Spoilage Investigation of Chill Stored Meagre (Argyrosomus regius) Using Modern Microbiological and Analytical Techniques - Faidra Syropoulou; Foteini F. Parlapani; Dimitrios A. Anagnostopoulos; Anastasios Stamatiou; Athanasios Mallouchos; Ioannis S. Boziaris (Foods, 2021)
Spoilage status of whole and filleted chill-stored meagre caught in January and July was evaluated using sensory, microbiological, 16S metabarcoding and Volatile Organic Compounds (VOCs) analysis. Based on the sensory analysis, shelf-life was 15 and 12 days for the whole fish taken in January and July, respectively, while 7 days for fish fillets of both months. For the whole fish, Total Viable Counts (TVC) at the beginning of storage was 2.90 and 4.73 log cfu/g for fish caught in January and July respectively, while it was found about 3 log cfu/g in fish fillets of both months. The 16S metabarcoding analysis showed different profiles between the two seasons throughout the storage. Pseudomonas (47%) and Psychrobacter (42.5%) dominated in whole meagre of January, while Pseudomonas (66.6%) and Shewanella (10.5%) dominated in fish of July, at the end of shelf-life. Regarding the fillets, Pseudomonas clearly dominated at the end of shelf-life for both months. The volatile profile of meagre was predominated by alcohols and carbonyl compounds. After univariate and multivariate testing, we observed one group of compounds (trimethylamine, 3-methylbutanoic acid, 3-methyl-1-butanol) positively correlating with time of storage and another group with a declining trend (such as heptanal and octanal). Furthermore, the volatile profile seemed to be affected by the fish culturing season. Our findings provide insights into the spoilage mechanism and give information that helps stakeholders to supply meagre products of a high-quality level in national and international commerce.